2019
DOI: 10.5334/labphon.67
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in phonetic perception: The joint influence of listener and talker characteristics on perception of the Korean stop contrast

Abstract: Where there is dialectal variability in production of a sound contrast, listeners from the two dialects may show parallel differences in perception. At the same time, perception is not static and can be influenced by other factors, including listeners' experience with, and expectations about, different talkers. This work examines perception of the Korean three-way stop phonation contrast by listeners of two dialects of Korean. We examine to what extent listeners' perception reflects production norms in their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Contrary to results reported by Niedzielski (1999), Hay et al (2006a, 2006b), Staum Casasanto (2008, 2009a, 2009b, Schertz et al (2019), and others, which showed that listeners adjust their perceptual strategies based on their prior knowledge of a targeted speech variety, we did not find evidence that listeners adjust their perceptual strategies based on the assumed identity of the talker. Specifically, we did not find for either the White or the Kleurling Afrikaans listeners that they were faster to fixate on the CVC target images in the Oral Only block for the White than for the Kleurling Afrikaans talker (Figure 11).…”
Section: Differential Perceptual Strategies Based On the Identity Of ...contrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to results reported by Niedzielski (1999), Hay et al (2006a, 2006b), Staum Casasanto (2008, 2009a, 2009b, Schertz et al (2019), and others, which showed that listeners adjust their perceptual strategies based on their prior knowledge of a targeted speech variety, we did not find evidence that listeners adjust their perceptual strategies based on the assumed identity of the talker. Specifically, we did not find for either the White or the Kleurling Afrikaans listeners that they were faster to fixate on the CVC target images in the Oral Only block for the White than for the Kleurling Afrikaans talker (Figure 11).…”
Section: Differential Perceptual Strategies Based On the Identity Of ...contrasting
confidence: 99%
“…For example, gestural overlap patterns that are language-specific (e.g., Beddor, Harnsberger, & Lindemann, 2002;Beddor & Krakow, 1999) or age group-specific (Harrington et al, 2008;Kleber, Harrington, & Reubold, 2012) have been shown to correspond to language-or age-specific perception in that the more extensive a speech community's production of coarticulatory overlap (e.g., coarticulatory vowel fronting or nasalization), the greater those language users' perceptual adjustments for the acoustic effects of that overlap. Other studies have shown language varietyand age-specific production and perception of coarticulation to be linked in that the group for which one type of information is especially informative perceptually is also the group that produces that information to a greater extent (Coetzee, Beddor, Shedden, Styler, & Wissing, 2018;Kuang & Cui, 2018;Schertz, Kang, & Han, 2019).…”
Section: The Relation Between the Perception And Production Of Coarti...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, the acoustic space used for the Spanish and English stimuli differed systematically. In a later study, Schertz, Carbonell, and Lotto () did find the expected differences when the ranges of the acoustic dimensions were controlled across languages, indicating that a purely auditory view cannot account for perceptual patterns. These sorts of group‐level comparisons of perception and production patterns across groups can provide one way to begin to tease apart the relative contribution of distributional, auditory, physiological, and general cognitive factors to cue use.…”
Section: Applications and Findingsmentioning
confidence: 88%
“…Kuang and Cui (2018) argue, via an apparent-time study, that a change in cue weighting from voice quality (phonation differences) to vowel quality (tongue root differences) in a register contrast in Southern Yi is led by changes in perception (see also Kleber, Harrington, & Reubold, 2012). Schertz, Kang, and Han (2019) show a change in the perception of the Korean stop contrast in a dialect where there is no evidence for a change in production, although they argue that this asymmetry more likely arises from exposure to dialectal variation rather than an incipient change. However, other work has found that production leads perception (Coetzee, Beddor, Shedden, Styler, & Wissing, 2018) or that the two modalities are aligned (Harrington, 2008).…”
Section: Sound Changementioning
confidence: 99%